Ответы и объяснения

Лучший Ответ!
2013-12-21T13:05:22+00:00
3а: 2√5 - √125 + 3√80 = 2√5 - 5√5 + 12√5 = 7√5
3б: √6 * 7√54 = √6 * 7 * 3 * √6 = 126
3в: (√162 - 10√2) * √2 = (9√2 - 10√2) * √2 = -2
3г: (3√98 - √128)÷√2 = 3√49 - √64 = 3 * 7 - 8 = 21 - 8 = 13
3д: 4√5t - 3/4 √80t - 12√(125t/9) = 4√5t - 3√5t - 20√5t = -19√5t
3e: (√c - 5√d)(√d - √c) = √cd - 5d - c + 5√cd = 6√cd - c - 5d
4a: (a√3 + √x)(a√3 - √x) = 3a² - x²
4б: (2√x - √3y)² = 4x - 4√3xy + 3y
4в: (√3 - √t)(3 + t + √3t) = 3√3 - t√t
5a: 11 + √11a = √11(√11 + √a)
5б: √10 - √35 = √5(√2 - √7)
5в: 25x² - 12 = (5x - 2√3)(5x + 2√3)
5г: 9x - 6√xy + y = (3√x - √y)²
5д: 6√n - 9√m + 4√mn - 6m = 2√n(3 + 2√m) - 3√m(3 + 2√m) = (2√n - 3√m)(3 + 2√m)
6a: (x² - 20) / (x√5 - 10) = (x - 2√5)(x + 2√5) / √5(x - 2√5) = (x + 2√5) / √5 = (x / √5) + 2
6б: (3a - 2√6ab + 2b) / (√27a³ - √8b³) = (√3a - √2b)² / ((√3a)³ - (√2b)³) = (√3a - √2b)² / ((√3a - √2b)(3a + √6ab + 2b)) = (√3a - √2b) / (3a + √6ab + 2b)
7a: 5 / √(5 - b) = 5√(5-b) / (5-b)
7б: (√3 + a) / (√3 - a) = (√3 + a)² / (3 - a²) = (3 + 2a√3 + a²) / (3 - a²)
8: (5√a / √b + 1 / √a) * (2√ab / (25a² - b)) = ((5a + √b) / √ab) * (2√ab / ((5a - √b)(5a + √b))) = 2 / (5a - √b)